1997
DOI: 10.1001/archsurg.1997.01430320105017
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Duration of Remission After Isolated Limb Perfusion for Melanoma

Abstract: Therapeutic ILP is an effective form of treatment for patients with recurrent and metastatic limb melanoma, achieving short- and long-term results that are superior to those achievable by any other form of treatment currently used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 11 publications
0
48
0
1
Order By: Relevance
“…Actinomycin D was used as well as melphalan because of the satisfactory response rates of this combination when administered by conventional ILP in our institution, without excessive toxicity. 2 For the duration of the ILI procedure (20-30 minutes), the infusate was continually circulated by repeated aspiration from the venous catheter and reinjection into the arterial catheter using a syringe attached to a 3-way tap in the external circuit. To increase the limb temperatures, a blood-warming coil was incorporated in the extracorporeal circuit, and the limb was encased by a hot-air blanket, with an overhead radiant heater placed over it.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinomycin D was used as well as melphalan because of the satisfactory response rates of this combination when administered by conventional ILP in our institution, without excessive toxicity. 2 For the duration of the ILI procedure (20-30 minutes), the infusate was continually circulated by repeated aspiration from the venous catheter and reinjection into the arterial catheter using a syringe attached to a 3-way tap in the external circuit. To increase the limb temperatures, a blood-warming coil was incorporated in the extracorporeal circuit, and the limb was encased by a hot-air blanket, with an overhead radiant heater placed over it.…”
Section: Methodsmentioning
confidence: 99%
“…In these patients, isolated limb perfusion (ILP) with melphalan is a suitable treatment option when other local treatments such as excision, cryotherapy, electrodesiccation, or laser ablation are no longer appropriate because of progressive disease. [1][2][3] Although results after ILP are satisfactory, the technique involves a complex and invasive surgical procedure with a substantial risk of complications. 4,5 Isolated limb infusion (ILI) has been developed at the Sydney Melanoma Unit as a simplified and minimally invasive alternative to ILP.…”
mentioning
confidence: 99%
“…157,158 Although other agents have been used for ILP, and many have yet to be tested, melphalan (L-phenylalanine mustard) is the cytotoxic agent most commonly used, often in combination with either actinomycin D or TNF-alfa. [158][159][160][161] Response rates after ILP have improved as the method has been refined. A large systematic review (n=2018 ILPs; 22 trials) found that for patients with unresectable stage IIIB-IIIC metastatic melanoma of the limbs, studies published between 1990 and 2008 reported a median overall response rate of 90% (range, 64%-100%) and a median complete response rate of 58% (range, 25%-89%).…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 99%
“…It requires simple devices. Since 1992, the Sydney Melanoma Center had performed ILI in over 300 patients in ten years, and its response rate for stage III melanoma was about 80%, during which no treatmentrelated amputation or death was reported (79). The response rate was significantly higher in patients >70 years than in those below 70 years (91 % vs. 78%, P<0.05).…”
Section: Lymph Node Dissectionmentioning
confidence: 99%